Business Sustainability: A Need To Re-Look Environmental Practices And Initiatives - Oribu, William; King’oriah, George; Agwata, Jones; Gongera, George Enock (European Journal of Business and Management, 2014)
Due to the increasing degradation of the natural business enterprises’ environmental commitment has become an important variable in most of today’s competitive business environment. This is because activities of most enterprises are the main causes of environmental degradation which in turn impact on the sustainability of their performance. This study looks at the specific business environmental practices and initiatives and how they impact on their sustainability. The overall objective of the study was to establish the impact of environmental initiatives on business sustainability around Lake Naivasha. The study design was descriptive survey in order to pick behaviors which needed to be mitigated for purposes of business sustainability. Purposive random sampling was used from the target population which comprised of farming, hospitality and fishing sectors. Discriminant analysis was used to analyze the data and the key findings of the study show that business sustainability depends mainly on the current environmental practices and initiatives that have been put in place. The study recommends that business associations be at the frontline in regulating activities by their members in order to achieve sustainability.
Keywords: Business Sustainability; Lake Naivasha, Environmental Initiatives; Enterprise Performance